A bypass case due to an acute inferior myocardial infarction caused by vascular occlusion of the left subclavian artery and left anterior descending artery - Altas Y (Therapeutics and Clinical Risk Management, 2016)
Yakup Altas, Ali Veysel Ulugg Department of Cardiology, Diyarbakir Gazi Yasargil Education and Research Hospital, Diyarbakir, Turkey Abstract: ST segment elevation is the most common electrocardiographic finding in acute myocardial infarction. ST elevation in chest leads generally represents left anterior descending artery occlusion, while elevation in DII and III, and aVF represents right coronary and circumflex artery occlusion. A female patient aged 66 years was admitted to our emergency service with ST elevation in leads DIII and aVF. A diagnosis of acute inferior myocardial infarction was made. The patient’s history included coronary artery bypass graft involving the left internal mammary artery to the left anterior descending coronary artery and aorta to the right coronary artery. The patient was taken to the cardiac catheterization laboratory for primary percutaneous coronary intervention and a lesion in the left anterior descending artery was identified. Additionally, the left subclavian artery was totally occluded. Following intervention to the lesion, the patient was discharged on day 4 of admission. Keywords: electrocardiography, myocardial infarction, coronary circulation